Dual activity of serum lipoprotein-associated phospholipase A2 yielding positive and inverse associations with cardiometabolic risk - Onat, Altan; Hergenc, Gulay; Can, Gunay; Ugur, Murat; Nartop, Filiz (WALTER DE GRUYTER GMBH, 2011)
Background: The clinical relevance of serum lipoprotein-associated phospholipase A(2) (Lp-PLA(2)) in populations prone to cardiometabolic risk needs exploration. We determined major covariates of Lp-PLA(2) mass, and its associations with cardiometabolic disorders. Methods: In 736 Turkish adults, serum total Lp-PLA(2) mass was determined by immunoassay. Its association with cardiometabolic risk was assessed in three categories. In a second sample of 98 subjects, enzyme protein in high-density lipoprotein (HDL) was also assayed after precipitation. Results: Significant inverse correlation existed with high triglyceride/low HDL cholesterol dyslipidemia, waist girth, apolipoprotein C-III, homeostatic model assessment, and linear inverse associations in women with lipoprotein (a) and fibrinogen, suggesting that Lp-PLA(2) mass reflected insulin sensitivity and that HDL bound enzyme mass dominated the associations. Among men, positive linear association with total cholesterol suggested additional association with low-density lipoprotein (LDL)-bound enzyme. High (>450 ng/mL) opposed to low (<210 ng/mL) circulating Lp-PLA(2) mass was associated with prevalent and incident coronary heart disease (CHD) in men. One SD increment in Lp-PLA(2) was associated with a 1.64-fold (95% CI 1.00; 2.70) likelihood of CHD, after adjustment for potential confounders. Furthermore, Lp-PLA(2) categories were significantly, independently and inversely associated in men with diabetes only (OR 0.61) and in women with metabolic syndrome only (OR 0.68), for a 1-SD increment. Conclusions: Serum total Lp-PLA(2) mass may indicate either elevated or diminished cardiometabolic risk, specific for gender, depending on its partitioning in lipoprotein groups.
Keywords: atherogenic dyslipidemia; coronary heart disease; diabetes type-2; lipoprotein-associated phospholipase A(2) mass; ACTIVATING-FACTOR ACETYLHYDROLASE; HIGH-DENSITY-LIPOPROTEIN; CORONARY-ARTERY-DISEASE; METABOLIC SYNDROME; CARDIOVASCULAR-DISEASE; POPULATION; DEFINITION; LP-PLA(2); PROTEIN; OBESITY; Medical Laboratory Technology